2020
DOI: 10.3390/foods9101448
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Characterization and Relative Quantification of α-Amylase/Trypsin Inhibitors from Wheat Cultivars by Targeted HPLC-MS/MS

Abstract: The α-amylase/trypsin inhibitors (ATIs) are discussed as being responsible for non-celiac wheat sensitivity (NCWS), besides being known as allergenic components for baker’s asthma. Different approaches for characterization and quantification including proteomics-based methods for wheat ATIs have been documented. In these studies generally the major ATIs have been addressed. The challenge of current study was then to develop a more comprehensive workflow encompassing all reviewed wheat-ATI entries in UniProt da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 38 publications
(65 reference statements)
0
26
0
Order By: Relevance
“…In this context, two commercially available wheat samples, whole meal and extracted wheat flour type 405 were analyzed. The analytical method used for the ATI analysis of wheat samples was the one developed in our previous work [ 20 ]. Compared to the average ATI contents in the two wheat samples, the results revealed that the relative amounts of ATIs were 2–3 times lower in sorghum samples SOR 1099, B-Sc, SOR 1236, SOR 958, SOR 20 and SOR 557 and up to 60 times lower in nine of the analyzed sorghum cultivars (SOR 777, SOR 618, R-Sc, SOR 654, SOR 759, SOR 226, SOR 1055, SOR 844 and SOR 555); while considering the corresponding averages ( Figure 4 a).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this context, two commercially available wheat samples, whole meal and extracted wheat flour type 405 were analyzed. The analytical method used for the ATI analysis of wheat samples was the one developed in our previous work [ 20 ]. Compared to the average ATI contents in the two wheat samples, the results revealed that the relative amounts of ATIs were 2–3 times lower in sorghum samples SOR 1099, B-Sc, SOR 1236, SOR 958, SOR 20 and SOR 557 and up to 60 times lower in nine of the analyzed sorghum cultivars (SOR 777, SOR 618, R-Sc, SOR 654, SOR 759, SOR 226, SOR 1055, SOR 844 and SOR 555); while considering the corresponding averages ( Figure 4 a).…”
Section: Resultsmentioning
confidence: 99%
“…The protein extraction and the in-solution digestion steps were based on the method established and optimized in our previous work [ 20 ] using ammonium bicarbonate (100 mM) buffer containing urea (4 M). Figure S7 (Supplementary Materials) provides the different extraction steps.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations